The study of temperature measurement based on the transmission of fixed wavelengths for helical long-period grating - Bai, Yunfeng; He, Zelong; Dang, Suihu (Oficyna Wydawnicza Politechniki Wrocławskiej, 2022)
This research involves a fixed wavelength and dual-wavelength ratio temperature measurement for helical long-period grating. There are two resonant dips near 1475 and 1520 nm, with the pitch length 782 μm. The temperature sensitivity of resonance wavelengths is about 0.06 nm/°C. Both theoretical simulation and experiment results show that the transmission of a fixed wavelength linearly changes with the temperature. It has a high application value for measuring temperature. Besides, the dual-wavelength ratio is studied to eliminate the influence of light source. The temperature sensitivity of transmission intensity ratio of I1469.6nm/I0 and I1469.6nm/I1526.5nm are about 1.0076/°C and 0.0155/°C, respectively, so the dual-wavelength ratio is more practical. And the 0.0155 times intensity change could be much more easily measured than the 0.06 nm wavelength change for each degree Celsius. So the dual-wavelength ratio of the helical long-period gratings is very suitable for temperature sensors.
Optica Applicata, Vol. 52, 2022, nr 1, s. 129-137
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; helical long-period grating; fixed wavelength; dual-wavelength ratio; temperature sensor